Fiscal transparency in recovery from the COVID-19 pandemic crisis - Małecka-Ziembińska, Edyta (Research Papers in Economics and Finance, 2021)
The aim of the article is to present the impact of unprecedented fiscal meas- ures taken in the context of the COVID-19 pandemic on fiscal transparency and to identify the role and importance of fiscal transparency in the process of recovering from the crisis. The conducted analysis proved that in the vast majority of countries around the world, the condition of public finances, measured by the deficit and pub- lic debt, has declined significantly as a result of measures taken to reduce the effects of the COVID-19 pandemic. These activities and strategies contribute to the lack of fiscal transparency. Meanwhile, fiscal transparency is an ally in recovering from the crisis. Strong fiscal frameworks (including numerical rules which promote fiscal pru- dence), backed by clear communication of policy priorities and fiscal transparency can meaningfully contribute to strengthening the credibility of public finances and reduce borrowing costs. These conclusions may be particularly important for emerging mar- ket economies and low-income developing countries, which find it more difficult and more expensive to obtain return sources of financing public investments.